“Sempre Vassalo Fiel de Sua Majestade Fidelíssima”: Os autos de vassalagem e as cartas patentes para autoridades locais africanas (Angola, segunda metade do século XVIII) - Ariane Carvalho da Cruz (Cadernos de Estudos Africanos)
This article discusses the association between war, militarization and political relations with local chiefs (sobas and dembos), often used as a resource for the development of business interests in Angola during the eighteenth century. Through the autos of vassalage signed by local chiefs and letters patent received by these men, it analyzes the relationship established between Portuguese and Africans. This article aims to better understand the dynamics of the slave trade, the incorporation of African posts in the Portuguese military structure and how the coexistence of Portuguese and African powers and hierarchies was a prerequisite for the maintenance of the Portuguese rule in Angola.